ANALISIS SISTEM MANAJEMEN PEMBELAJARAN TATAP MUKA PADA MASA PANDEMI COVID-19 DI SMA KRISTEN RANTEPAO - Hendrik Palinggi; Witarsa Tambunan (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2021)
The objectives of writing this study were to: 1) to obtain the best methods and techniques in the limited face-to-face learning management system in Rantepao Christian Senior High School; 2) contributing advice to the school management team in order to improve the quality of learning during the Covid 19 pandemic; 3) contributing advice to educators and education personnel in order to improve face-to-face learning management during the COVID-19 pandemic. The method used in this writing is a qualitative method with a literature review approach and participant responses via google form to students and teachers at Rantepao Christian High School. In the analisis using the problem tree approach, target tree, and alternative solution tree in getting the expected results. The results show that the impact of a learning management system that is suitable for school conditions can provide time-effective and cost-efficient convenience for students and teachers in achieving learning objectives. Keywords: learning management, face-to-face learning, Covid-19 pandemic